The psychology of linking crimes: a review of the evidence - Woodhams, Jessica (Legal and criminological psychology, 2007)
Purpose. This paper is concerned with case linkage, a form of behavioural analysis used to identify crimes committed by the same offender, through their behavioural similarity. Whilst widely practised, relatively little has been published on the process of linking crimes. This review aims to draw together diverse published studies by outlining what the process involves, critically examining its underlying psychological assumptions and reviewing the empirical research conducted on its viability. Methods. Literature searches were completed on the electronic databases, PsychInfo and Criminal Justice Abstracts, to identify theoretical and empirical papers relating to the practice of linking crimes and to behavioural consistency. Results. The available research gives some support to the assumption of consistency in criminals' behaviour. It also suggests that in comparison with intra-individual variation in behaviour, inter-individual variation is sufficient for the offences of one offender to be distinguished from those of other offenders. Thus, the two fundamental assumptions underlying the practice of linking crimes, behavioural consistency and inter-individual variation, are supported. However, not all behaviours show the same degree of consistency, with behaviours that are less situation-dependent, and hence more offender-initiated, showing greater consistency. Conclusions. The limited research regarding linking offenders' crimes appears promising at both a theoretical and an empirical level. There is a clear need, however, for replication studies and for research with various types of crime.